Comparative determination of placental perfusion by magnetic resonance imaging and contrast-enhanced ultrasound in a murine model of intrauterine growth restriction. (September 2018) - Arthuis, C.-J.; Mendes, V.; Même, S.; Même, W.; Rousselot, C.; Winer, N.; Novell, A.; Perrotin, F.
Abstract: Introduction: Exploration of placental perfusion is essential in screening for dysfunctions impairing fetal growth. The objective of this study was to assess the potential value of contrast-enhanced ultrasonography (CEUS) and magnetic resonance imaging (MRI) for examining placental perfusion in a murine model of intrauterine growth restriction (IUGR). We also studied the reproducibility of perfusion quantification by CEUS. Methods: Pregnant Sprague Dawley rat models of IUGR were studied during the third trimester. Unilateral uterine artery ligation induced IUGR. Placental perfusion was evaluated by CEUS and perfusion MRI with gadolinium for both ligated and control fetoplacental units. The kinetic parameters of the two imaging modalities were then compared. Results: The analysis included 20 rats. The study showed good reproducibility of the CEUS indicators. The CEUS perfusion index approximated the blood flow rate and was halved in the ligation group (27.9 [u.a] (±14.8)) versus 61 [u.a] (±22.3) on the control side ( P = 0.0003). MRI with gadolinium injection showed a clear reduction in the blood flow rate to 51.2 mL/min/100 mL (IQR 34.9–54.9) in the ligated horn, compared with 90.9 mL/min/100 mL (IQR 85.1–95.7) for the control side ( P < 0.0001). The semiquantitative indicators obtained from the kinetic curves for both CEUS and MRI showed similar trends. Nonetheless, values were more widely dispersed with CEUS than MRI. Discussion: The similar results for the quantification of placental perfusion by MRI and CEUS reinforce the likelihood that CEUS can be used to identify IUGR in a murine model induced by uterine vessel ligation. Highlights: Uterine Doppler currently allow the diagnosis of IUGR, albeit with low sensitivity. CEUS and MRI can be used to quantify the maternal placental vascularization. This study is the first to compare MRI and CEUS for studying placental perfusion. CEUS quantitative indicators of the vascular uptake phase are especially interesting. CEUS and MRI results showed similar trends for each parameter.